KDOQI 2019 Vascular Access Guidelines: What Is New - Lok, Charmaine E.; Rajan, Dheeraj K. (Seminars in Interventional Radiology, 2022)
The new Kidney Disease Outcomes Quality Initiative (KDOQI) Vascular Access Guidelines have a patient focus for comprehensive vascular access management. The patient's unique circumstances and individualized needs are the foundation of their dialysis access strategy, which is interlinked with the patient's End Stage Kidney Disease (ESKD) Life-Plan. The ESKD Life-Plan is an individualized and comprehensive map for dialysis modalities and vascular access for the lifetime of the patient. New targets are introduced that align with this patient-centered approach. They are less detail prescriptive than prior vascular access guidelines, giving opportunity for vascular access management at the clinician's discretion, partly in consideration of constraints of local resources and available expertise; however, the guidelines also emphasize the importance of high-quality standards with defined targets for achieving the guideline's overarching goal for vascular access care. The guidelines made significant changes relevant to the interventionalist, including selective use of vessel mapping in planning for vascular access, choice of vascular access that allows for considering endovascular access creations, and endovascular treatment (e.g., angioplasty, stent graft insertions) based on clinical indicators found on routine clinical monitoring. To that end, preemptive angioplasty of fistulas and grafts with stenosis, not associated with clinical indicators, is not recommended. New content in these guidelines also includes the use of stent grafts and management of central venous stenosis. The new KDOQI Vascular Access Guidelines 2019 represent a rigorous review of the evidence; however, the available evidence to guide vascular access practice remains limited. There is a significant need and opportunity for new and ongoing high-quality research to inform best practice.
Keywords: hemodialysis; vascular access; chronic kidney disease; end-stage kidney disease; guideline; interventional radiology